SUBSTITUSI TEPUNG BONGGOL PISANG PADA MIE BASAH DENGAN PENAMBAHAN KULIT BUAH NAGA (Hylocereus undatus) - Sumardana, Gede; Syam, Husain; Sukainah, Andi (Universitas Negeri Makassar, 2017)
This study aims to determine the effect of substitution of banana tuber flour and the addition of super red dragon fruit skin extract to the quality of wet noodles. This study consists of two stages, the first step is to find the best concentration between wheat flour and banana tuber flour in the making of wet noodles and the second stage is the addition of super red dragon fruit skin extract. The research method used is complete randomized design (RAL), the research data is processed by ANOVA variance analysis technique with further test of DMRT (Duncan Multiple Rate). The results of the Phase 1 study showed that the substitution of wheat flour from banana tuber flour 285 g : 15 g was the best treatment with hedonic characteristics for flavor 3,57, color 3,69, aroma 3,43, and texture 3, 61. Phase 2 research showed that the wet noodle without the addition of red dragon fruit skin extract is the best treatment with hedonic characteristic for taste of 3,53, color 3,21, flavour 3,31 and texture 3,41 with water content 58,14%, ash 0,72%, 0.48% fiber content, and antioxidant levels of 1.01.